Penerapan RMS Contrast sebagai Penentu Citra Terbaik Berdasarkan Tingkat Kontras - Shiennyta Florensia Adiriyanto; I Gede Arta Wibawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
This research centers on the objective of identifying the finest image from a burst shot through the utilization of Root Mean Square (RMS) contrast as a guiding metric. The primary focus lies in selecting the visually captivating image by assessing the contrast levels present in each individual shot. By conducting calculations of the RMS contrast values, the optimal image can be determined. The core purpose of this study is to employ RMS contrast as a reliable criterion for selecting the most outstanding image from a burst shot, thereby guaranteeing the production of high-quality visuals, and aiding in the organization and decluttering of smartphone galleries. This research holds significance in addressing the growing need for efficient and effective image selection methods, ensuring that users can effortlessly identify and showcase the best images captured in burst mode. By embracing the power of RMS contrast analysis, individuals can confidently curate their image collections with exceptional visual content while optimizing limited storage space on their smartphones.